A HARD TIME TO DATE: THE SCOTT COUNTY PUEBLO (14SC1) AND PUEBLOAN RESIDENTS OF THE HIGH PLAINS. Issue 1 (7th December 2017) - Hill, Matthew E.; Beck, Margaret E.; Lengyel, Stacey; Trabert, Sarah J.; Adair, Mary J.
Abstract : During the seventeenth and eighteenth centuries, Puebloan women (if not entire families) were incorporated into Apache Dismal River communities in western Kansas. In at least one site (14SC1), Puebloan people lived in a small masonry pueblo. We evaluate the timing and nature of the Puebloan occupation at 14SC1 and its relationship to the Dismal River population at the site. We use a Bayesian analytical framework to evaluate different models of the pueblo's use history, constraining 12 radiocarbon dates by their stratigraphic data and then comparing this framework with different temporal models based on the historical record. We conclude that Dismal River people lived at 14SC1 prior to the appearance of Pueblo migrants, sometime between cal AD 1490 and 1650. Construction and early use of the pueblo by migrants from the Rio Grande valley occurred between cal AD 1630 and 1660, and the pueblo was closed by burning sometime between cal AD 1640 and 1690. Site 14SC1 lacks Rio Grande Glaze Ware, and its residents seem rarely to have engaged with the groups in the Southern Plains Macroeconomy. Our results contribute to studies of indigenous community formation and Puebloan residential mobility during the Spanish colonial period. Abstract : Durante los siglos XVII y XVIII, las mujeres Pueblo (o posiblemente familias enteras) fueron incorporadas a las comunidades Apaches de la cultura Dismal River en Kansas occidental. Por lo menos en un sitio (14SC1), los indígenas Pueblo vivieron en un pequeño poblado de mampostería. Evaluamos la cronología y la naturaleza de la ocupación Pueblo en 14SC1 y su relación con la ocupación Dismal River en el sitio. Usamos un marco analítico bayesiano para evaluar diferentes modelos de la cronología ocupacional del pueblo, delimitando los rangos de doce fechas de radiocarbono por sus posiciones estratigráficas y luego comparando este marco con diferentes modelos temporales basados en el registro histórico. Concluimos que los indígenas Dismal River vivieron en 14SC1 antes de la aparición de los migrantes Pueblo en algún momento entre 1490 y 1650 cal dC. La construcción y el uso inicial del pueblo por migrantes procedentes del valle del Río Grande ocurrió entre 1630 y 1660 cal dC, y el pueblo fue cerrado por un incendio entre 1640 y 1690 cal dC. El sitio 14SC1 carece de vajillas del estilo Río Grande con engobe, y sus residentes parecen haber tenidos interacciones limitadas con los grupos que participaron en la macroeconomía de las Planicies del Sur. Nuestros resultados contribuyen al estudio de la formación de comunidades indígenas y la movilidad residencial Pueblo durante el período colonial español.